Fragilidade e utilização de cuidados de saúde em idosos com Doença Renal Crônica: insights do ELSI-Brasil - Giraldes, Ana Paula Rosim (2024)
Chronic kidney disease (CKD) is a health condition that causes progressive and permanent changes in the function or structure of the kidneys for at least three months, with health implications. According to the International Society of Nephrology, CKD affects about 10% of the world's population and is more common in people over 65. And in addition to chronic diseases related to CKD, there is frailty, which worsens as CKD advances. It can be characterized by accumulating deficits in functionality, mobility, and chronic disease factors. The severity of these deficits is directly related to poor clinical outcomes, reducing the individual's ability to cope with health-related challenges. Objectives: This study utilized data from the ELSI-Brazil (Longitudinal Study of the Health of the Brazilian Elderly) survey to assess levels of frailty and its impact on healthcare utilization among older people with CKD residing in the Brazilian community. Methods: This is a secondary data analysis from the second wave of the ELSI Brazil study (2019 to 2021). A self-reported questionnaire was used to identify individuals with CKD. The Frailty Index (FI), which is based on factors such as comorbidities, disabilities, and functional capacity, was also used to assess the level of frailty. Moreover, Andersen and Newman's healthcare utilization model was used to evaluate the use of healthcare resources. Results: The overall sample exhibited a weighted mean FI score of 0.19 (95% CI, 0.18-0.20). Notably, individuals with CKD displayed higher levels of frailty (FI = 0.28; 95% CI, 0.25-0.31). In the past 12 months, approximately 84% of individuals with CKD visited a medical professional, with nearly 65% being frail. Furthermore, a significantly positive association was found between higher levels of frailty index and an increased probability of medical visits and hospitalization in the past year. Conclusions: Elderly people in Brazil suffering from CKD are prone to high levels of frailty. The adverse effects of this condition, such as lowered perceived health status and increased hospitalization rates, demand immediate action. We strongly encourage healthcare systems to establish programs for prompt identification and treatment of frailty in this group of patients.